IMPLEMENTATION OF WASTE BANK PROGRAM IN BENGKULU CITY - Nurcayani, Anggi; Hakim, Kahar; Hardayani, Yorry (Perkumpulan Dosen Muda (PDM) Bengkulu, 2024)
Every year Indonesia produces tens of millions of tons of waste. This causes an increasing amount of waste to pile up in landfills which must be addressed immediately. The waste bank program is one program that is considered to be a solution that can reduce the problem of waste produced by the community. However, even though there are many waste banks in existence, the waste problem has not yet been resolved. The number of closed waste banks also raises the question of why this waste bank program cannot run well. This research aims to find out and provide an overview of the reasons why the implementation of the waste bank program in Bengkulu City has not gone well. This research uses descriptive qualitative methods. This research aspect uses Nugroho's theory and is guided by the Regulation of the Minister of Environment and Forestry of the Republic of Indonesia Number 14 of 2021 concerning Waste Management at Waste Banks. Data collection techniques consist of observation techniques, interview techniques, documentation techniques, library research. The research results show that the implementation of the waste bank program in Bengkulu City is still less effective because there are still many obstacles starting from the pre-implementation, implementation and post-implementation aspects. In the pre-implementation aspect, there is still uneven distribution to the community, but in the policy refinement stage it is quite good. In the implementation aspect, the bank program has not been able to run optimally due to various obstacles that have not been met in terms of management criteria, facilities and governance of the waste bank program. In the post-implementation aspect, the waste bank program is considered not to be an effective solution because there is still very little waste being reduced, low community participation, many waste banks have closed, and the government's role is still very limited.